DIAGNOSTIC TOOLS FOR DETERMINING THE LEVEL OF INVOLVEMENT OF CHILDREN IN HOCKEY - Naboichenko, E.S.; Istomin, S.O. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the level of involvement of children aged 5-7 years in hockey (sports activities). Methods and structure of the study. In the course of scientific work, the following were carried out: interviewing; pedagogical observation; method of studying the products of activity; conversation; testing the general, special and technical readiness of young hockey players aged 5-7 years (n=120), who are engaged in the Sports School of the Olympic Reserve "Spartakovets" in order to determine the level of participation over a period of three years (2014-2016). Results and conclusions. Children 5-7 years old with an active level of participation in hockey have in the future: one hundred percent enrollment rate; high sports results of the implementation of the sports training program for the sport of hockey in full. The presented results can be used as indicative norms for the selection of young hockey players for the initial stage.